Conservation and Enhanced Binding of SARS-CoV-2 Omicron Spike Protein to Coreceptor Neuropilin-1 Predicted by Docking Analysis - Piyush Baindara; Dinata Roy; Santi M. Mandal; Adam G. Schrum (MDPI AG, 2022)
The Omicron variant of SARS-CoV-2 bears peptide sequence alterations that correlate with a higher infectivity than was observed in the original SARS-CoV-2 isolated from Wuhan, China. We analyzed the CendR motif of spike protein and performed in silico molecular docking with neuropilin-1 (Nrp1), a receptor-ligand interaction known to support infection by the original variant. Our analysis predicts conserved and slightly increased energetic favorability of binding for Omicron CendR:Nrp1. We propose that the viral spike:Nrp1 coreceptor pathway may contribute to the infectivity of the Omicron variant of SARS-CoV-2.